Evaluating the safety and efficacy of novel mRNA vaccines for infectious diseases - Nanda, Naimish; Syed Sabir Ali, Syed Sajid Ali (Journal of Neonatal Surgery, 2025)
In recent years, the advent of messenger RNA (mRNA) vaccine technology has revolutionized the landscape of infectious disease prevention. Unlike traditional vaccines, mRNA vaccines leverage a synthetic strand of mRNA encoding specific antigens, which, upon delivery into the host cells, triggers an immune response without introducing live or attenuated pathogens. This study evaluates the safety and efficacy of novel mRNA vaccines designed for a range of infectious diseases, with a particular focus on SARS-CoV-2, influenza, and emerging zoonotic viruses. The research employs a multi-phase methodology comprising preclinical and clinical trials. Preclinical studies assess the immunogenicity and safety profile in animal models, highlighting mRNA stability, delivery efficiency, and immunotoxicity. The clinical trials, spanning phases I through III, involve diverse populations, including pediatric, adult, and immunocompromised groups. Key endpoints include antibody titers, cellular immune responses, and the incidence of adverse events. Preliminary findings demonstrate a favorable safety profile, with mild to moderate reactogenicity reported in most cases. The efficacy, measured by neutralizing antibody levels and real-world protection against infections, exceeds 90% in several candidate vaccines. Additionally, the modular design of mRNA vaccines facilitates rapid adaptation to emerging pathogens, offering a significant advantage in outbreak scenarios. Despite promising results, challenges persist, such as cold-chain logistics, long-term durability of immunity, and addressing vaccine hesitancy. This research underscores the transformative potential of mRNA vaccines in combating infectious diseases while emphasizing the need for continuous monitoring and innovation to address limitations.